French Tragedy : Scenes of Civil War, Summer 1944 - Todorov, Tzvetan, 1939-2017 (Book collections on Project MUSE., 1996)
Finding similar failures on both sides, he also cites "a qualitative difference between the two, an irreducible asymmetry, which resides in their ideals, in totalitarianism versus democracy." Suspenseful, compelling, and uncompromisingly honest, A French Tragedy goes beyond the events themselves to ponder the nature of sacrifice, of suffering, and of individual responsibility in a world where civil war still thrives.